SCIENTIFIC AND MATHEMATICAL LITERACY IN BASIC EDUCATION: A PERSPECTIVE ON STUDENT PERFORMANCE - Cazuza da Silva Neto, Raimundo (Journal of Interdisciplinary Debates, 2023)
This study aims to understand the factors that led to low performance in proficiency and scientific and mathematical literacy in basic education, according to the results of the last PISA, which statistically analyzes the OECD countries of Latin America of which Brazil is a part. As a methodology adopted, literature, books, articles, statistical data from the last six years were analyzed, this exposed problem cannot be solved in the short or medium term, however, collectively the solutions are necessary and urgent, campaigns to encourage reading, recycling, continuity of teachers’ studies, professional development, reducing social inequalities, among others, are actions that will make all the difference in changing the reality of Brazilian students.